2001
DOI: 10.1002/1615-9861(200110)1:10<1327::aid-prot1327>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Identification of androgen-regulated genes in the prostate cancer cell line LNCaP by serial analysis of gene expression and proteomic analysis

Abstract: A common therapy for nonorgan-confined prostate cancer involves androgen deprivation. To develop a better understanding of the effect of androgen on prostatic cells, we have analyzed gene expression changes induced by dihydrotestosterone (DHT) in the androgen responsive prostate cancer line LNCaP, at both RNA and protein levels. Changes at the RNA level induced by DHT were determined by means of serial analysis of gene expression (SAGE), and protein profiling was done by means of quantitative two-dimensional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 16 publications
6
53
1
Order By: Relevance
“…This correlation is at least as good as previous SAGE papers in which between 7 and 50% of differentially expressed tags were not corroborated (Zhang et al, 1997;Hibi et al, 1998;de Waard et al, 1999;Waghray et al, 2001). Moreover, although mRNA abundance can be a poor indicator of protein levels (Pradet-Balade et al, 2001), we found that, for a given gene, the relative level of mRNA in different samples correlated well with the relative protein level as gauged by immunohistochemical staining (Figure 2).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This correlation is at least as good as previous SAGE papers in which between 7 and 50% of differentially expressed tags were not corroborated (Zhang et al, 1997;Hibi et al, 1998;de Waard et al, 1999;Waghray et al, 2001). Moreover, although mRNA abundance can be a poor indicator of protein levels (Pradet-Balade et al, 2001), we found that, for a given gene, the relative level of mRNA in different samples correlated well with the relative protein level as gauged by immunohistochemical staining (Figure 2).…”
Section: Discussionsupporting
confidence: 87%
“…These numbers are slightly smaller than those in other recent SAGE publications, with upwards of 20 000 tags (Zhang et al, 1997;Hibi et al, 1998;Nacht et al, 1999;Velculescu et al, 1999;Hough et al, 2000;Waghray et al, 2001). However, the global distribution of genes in our gastric libraries is Figure 1 Northern blotting for selected genes identified by SAGE.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Prostate cancer is dependent on the action of androgens, and PLZF has been shown to be an androgen-responsive gene (Jiang and Wang, 2004). LYRIC/AEG-1 is upregulated in response to androgens (Waghray et al, 2001).…”
mentioning
confidence: 99%
“…We consider the discrepancies were caused by the following reason: several reports told that correlation between mRNA and protein levels was insufficient to predict protein expression levels from quantitative mRNA data. 40,41 The proteomic approach is considered to have a capability of finding biomarkers other than those found by genomic approach. We stratified the cancer-related proteins into seven functional categories based on the prostate expression database (PEDB).…”
Section: Proteome Of Prostate Cancer H Kuruma Et Almentioning
confidence: 99%